Re-Examination of the Meaning of Masyarakat and Warga Vis-A-Vis Technological and Social Changes (Jurnal Bahasa, 2023)
This paper intends to re-examine the meaning of the words masyarakat and warga due to the effect of technological and social changes. A preliminary examination in Tesaurus Bahasa Melayu Dewan (2015), Kamus Dewan Edisi Pertama (1970) and Kamus Dewan Perdana (2021) found that the two words are neither synonymous nor depict a clear relationship with one another. However, a cross-referencing analysis from the WebCorp database indicates a possible association between the words due to the effect of technological and social changes. The three words that form this association are "massa", "siber" and "internet". They showed features that clearly explain the meaning of technological and social changes. Based on the analysis of the WebCorp database, the acquired detailed lexical use of masyarakat and warga not only presents their definition, but also their associated activities, hopes and behaviours in relation to "massa", "siber" and "internet". This paper may serve as a stepping stone to explain problem areas in the meaning of both masyarakat and warga, and as a catalyst for lexicographers to scrutinize and re-examine their meaning in order to improve existing dictionary entries.Keywords: Masyarakat, warga, massa, siber, internet, semantic changeFull text: PDF